ANALISIS KASUS TENTANG PUTUSAN PENGADILAN NO 92/PDT.BTH/2019/PN MTR TENTANG HARTA KEKAYAAN PERUSAHAAN - Fresilia Twins Bamasaq; H. Arba Arba (Private Law, 2023)
This study aims to determine the position of the status of ownership of land rights jointly with a company registered in the name of one person and to find out the judge's consideration in deciding the case No. 92/pdt.bth/2019/PN Mtr. This research uses normative juridical research methods. Normative juridical research is library legal research. The results showed that the proof of ownership of land purchased privately by the managing director who is bound in marriage which is controlled and used for the company's business activities is juridically the property of the managing director and his wife. The judge's consideration in deciding the case is that the resistance filed by the plaintiff is rejected because the land certificate is in the name of the allied partners and there is no written evidence including authentic evidence that can prove that the land belongs to the company even though the land is controlled and used by the company. It is hoped that the government will conduct counseling for business actors, especially CVs, to avoid cases of borrowing the names of their allies.